2021
DOI: 10.3389/fped.2021.679203
|View full text |Cite
|
Sign up to set email alerts
|

Acid Suppression Use Among Infants in One Tertiary Children's Hospital in China, 2015–2018: A Retrospective Observational Study

Abstract: Clinical guidelines emphasized that physicians should be cautious when prescribing acid suppressions to infants. Histamine-2 receptor antagonists (H2RAs) and proton pump inhibitors (PPIs) are not approved for use in infants aged below 2 years in China. We investigated H2RA/PPI use in infants aged below 2 years hospitalized between 1st January 2015 and 31st December 2018 in a Chinese tertiary children's hospital. Our study observed that H2RAs/PPIs were frequently prescribed with a prevalence of 4.4% (7,158/162,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The authors reported that H2RAs/PPIs were commonly prescribed (prevalence: 4.4%), PPI use being over two times more frequent than H2RA use (71.9% vs. 28.1%). Unexpectedly, the study's findings showed that H2RAs/PPIs were commonly used (57.5%) in the treatment of infants without digestive system diseases, mostly suffering from respiratory diseases including asthma and acute upper respiratory tract infections ( 37 ).…”
Section: Prescribing Patterns Of Antisecretory Medicationsmentioning
confidence: 99%
“…The authors reported that H2RAs/PPIs were commonly prescribed (prevalence: 4.4%), PPI use being over two times more frequent than H2RA use (71.9% vs. 28.1%). Unexpectedly, the study's findings showed that H2RAs/PPIs were commonly used (57.5%) in the treatment of infants without digestive system diseases, mostly suffering from respiratory diseases including asthma and acute upper respiratory tract infections ( 37 ).…”
Section: Prescribing Patterns Of Antisecretory Medicationsmentioning
confidence: 99%
“…PPIs are preferred to H2RAs in reducing GERD symptoms in adults [17]. Despite the lack of published data about the efficacy of acid suppressants and increasing worries about their complications, oral PPIs have been increasingly used in infantile (under one year of age) GERD [18,19]. In recent guidelines, a 4-week trial of a PPI or H2RA for infants with symptoms such as unexplained feeding difficulties, bizarre behavior, and unsuitable weight gain, along with significant regurgitation, has been suggested [9].…”
Section: Acid-suppressantsmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are gastric acid-suppressive medication, frequently (over-) prescribed and used in all age-groups [ 1 5 ], also during the first years of life [ 6 11 ]. Although there is no clear consensus on the indications or duration of use in pediatrics [ 12 ], PPIs are among the most common off-label used medications in infants and young children [ 10 , 13 , 14 ]. The broad range of pediatric and especially neonatal indications include (presumed) gastro-esophageal or laryngopharyngeal reflux, prevention and treatment of stress ulcers, eosinophilic esophagitis and infantile colic [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%